Risk management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Risk analysis in dryland farming systems by Jock Anderson and John Dillon 1992 109pp ISBN 92 5 103204 1 Pbk Publications Division, FAO Via delle Terme di Caracalla 00100 Rome, ITALY